Archiwum Diecezjalne w Rzeszowie. Powstanie, zasób i działalność - Nabożny, Marcin (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The article focuses on the establishment, fonds and activity of the Diocesan Archive in Rzeszów. The Archive in Rzeszów plays an important role. Its purpose is to protect, collect, organise, permanently store the archival materials and make them available. The Diocese of Rzeszów was established by John Paul II in his bull Totus Tuus Poloniae Populus of 25 March 1992. The Diocesian Archive in Rzeszów is a separate scientifi c and cultural institution established by the Bishop of Rzeszów, Kazimierz Górny. It is located at the seat of Diocesian Curia in Rzeszów at Castle Street 4. In the years 1992-1999 the Rev. Dr Stanisław Nabywaniec was responsible for organizing the Archive. In 1999 this task was assigned to the Rev. dr Andrzej Motyka, who was also appointed the Diocesan Archive Director. Soon, the statute and the rules of the Archive were formulated, the structure was established and it became the basis for organising the archival materials. The materials have been available since 2003. The article presents the role of the historical archive in the diocese, the origins of the Diocese of Rzeszów, the aims and tasks of the Diocesan Archive in Rzeszów. Then, it focuses on the statute, the rules and organization of the Archive. A significant element of the article is the collection of the Diocesan Archive in Rzeszów (the collection structure) which contains 35 fonds. The final part shows the details about church archives, where we can fi nd archival materials relating to the current area of the Diocese of Rzeszów, which was formed from parts of the Diocese of Przemyśl and Tarnów. Previously, this area was the part of the Metropolis of Lvov and Krakow. The paper also provides the list of archives helpful to the researchers of history of the mentioned area: the Archive of the Metropolitan Curia in Krakow, the Archive of the Cathedral Chapter of Krakow, Archbishop Eugeniusz Baziak Archive, the Archdiocesan Archive of Latin Rite in Przemyśl, the Archive of the Cathedral Chapter of Przemyśl, the Archive of Cathedral Chapter of Sandomierz and the Archive of the Diocese of Tarnów. The article contains the current contact details for these institutions, directors, opening hours, and the list of guides and articles about fonds. The paper is the first comprehensive study of the Diocesan Archive in Rzeszów as it has been not presented in the previous studies of the Archives of the Catholic Church in Poland.